2018
DOI: 10.1177/0961203318785245
|View full text |Cite
|
Sign up to set email alerts
|

Medical adherence in patients with systemic lupus erythematosus in Germany: predictors and reasons for non-adherence – a cross-sectional analysis of the LuLa-cohort

Abstract: Objective Adherence to medication has a major impact on treatment control and success especially in chronic diseases but often remains unrecognized. Besides clinical, socioeconomic, disease-related and treatment-related parameters, general and personal health beliefs, as well as perception of health, can affect adherence. Our aim was to investigate the adherence to lupus-specific medications in German lupus patients and to assess influencing factors including detrimental or beneficial effects of health percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 46 publications
0
26
0
1
Order By: Relevance
“…The incidence of non-adherence at any time during a 6-month study of methotrexate use in patients with rheumatoid arthritis was 26%, 3 and only 63% of patients with systemic lupus erythematosus reported high medication adherence in another study. 4 A recent report investigated medication adherence in medical practices in the United Kingdom. It highlights the complexity of the causes of non-adherence and the need to improve adherence, particularly in people with chronic conditions, and concludes that there is a need for more and better research into behavioral patterns and adherence issues in patients with chronic disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of non-adherence at any time during a 6-month study of methotrexate use in patients with rheumatoid arthritis was 26%, 3 and only 63% of patients with systemic lupus erythematosus reported high medication adherence in another study. 4 A recent report investigated medication adherence in medical practices in the United Kingdom. It highlights the complexity of the causes of non-adherence and the need to improve adherence, particularly in people with chronic conditions, and concludes that there is a need for more and better research into behavioral patterns and adherence issues in patients with chronic disease.…”
Section: Introductionmentioning
confidence: 99%
“…One of the factors associated with better adherence was higher age. 4 A cross-sectional survey which analyzed 577 questionnaires from patients with chronic conditions also found that adherent subjects were older. More adherent patients also took more medications, were in better spirits and had greater confidence in, and information about, their treatments.…”
mentioning
confidence: 99%
“…Indeed, a review on adherence in autoimmune conditions also concluded that economic, demographic, and clinical characteristics were only moderately linked to adherence or persistence (21). The ndings on the prospective association of beliefs about medication with adherence and persistence in medication taking is congruent with previous work in other conditions (37)(38)(39). Still, beliefs about medication were scarcely studied among PwMS; the only study that examined adherence to DMTs was cross-sectional and found no association between medication beliefs and adherence (13).…”
Section: Discussionmentioning
confidence: 57%
“…Despite the widely known benefits of AMA on SLE disease activity and course, non-adherence remains a major problem [ 14 , 39 , 40 ]. Costedoat-Chalumeau et al found that the most common reasons for AMA treatment discontinuation by patient initiative included the perception of AMA not being an effective treatment and apprehension about potential side-effects [ 41 ].…”
Section: Discussionmentioning
confidence: 99%